PENGELOLAAN AIR MINUM BERBASIS MASYARAKAT Studi Kasus Pembangunan Air Minum Di Desa Nelayan II Kabupaten Sungai Liat, Propinsi Bangka-Belitung - Yudo, Satmoko (Center for Environmental Technology, 2005)
According to the result of the World Bank study, from 121 drinking water management projects in rural area, only 20 (16,6%) are very effective projects. A lot of drinking water management in developing country, including Indonesia is not running well. One of the reasons of this problem is that community did not take part in developing and managing drinking water treatment plant. A right policy and strategy could overcome the problem and give an effective and sustainable of drinking water management.This paper generally explain principles and general policy in developing the drinking water treatment plant and how to apply the strategies, therefore that it is running well and the are will being of the community sustainable.There is also an example, a case study about small-scale drinking water treatment plant in a fisherman village, Sungai Liat, Province Bangka-Belitung where the community took part in every stage of building it.Ã‚Â Keywords: Community based of drinking water management, policy of developing the drinking water treatment plant, application of strategies